2002
DOI: 10.1097/00007890-200203270-00022
|View full text |Cite
|
Sign up to set email alerts
|

Improved clinical outcomes for liver transplant recipients using cyclosporine monitoring based on 2-hr post-dose levels (C2)1

Abstract: Using C2 monitoring, the overall incidence of acute cellular rejection was lower compared with the C0 group, and the histological severity of acute rejections was shown to be significantly milder for the C2 group, indicative of good long-term prognosis. These data demonstrate that the use of C2 monitoring is superior to C0 and results in a reduction in the incidence and severity of acute cellular rejection without detrimental effect on the drug safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(104 citation statements)
references
References 15 publications
7
95
1
1
Order By: Relevance
“…10,28 Although 2 h blood CSA concentrations in humans are predictive of acute rejection and clinical outcome in solid organ transplantation, a study of 97 dogs with AD treated with CSA at a mean dose of 4.6 mg ⁄ kg orally once daily for 28 days found no significant correlation between clinical improvement and whole blood CSA concentrations. 27,28,31,32 As skin is likely to be the target organ for treatment of atopic dermatitis, the concentration of CSA achieved in the skin may be important in determining the clinical response to CSA therapy. This is further exemplified by the moderate correlation between skin and whole blood CSA concentrations in our study, which indicates that whole blood concentrations do not accurately predict CSA concentrations in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…10,28 Although 2 h blood CSA concentrations in humans are predictive of acute rejection and clinical outcome in solid organ transplantation, a study of 97 dogs with AD treated with CSA at a mean dose of 4.6 mg ⁄ kg orally once daily for 28 days found no significant correlation between clinical improvement and whole blood CSA concentrations. 27,28,31,32 As skin is likely to be the target organ for treatment of atopic dermatitis, the concentration of CSA achieved in the skin may be important in determining the clinical response to CSA therapy. This is further exemplified by the moderate correlation between skin and whole blood CSA concentrations in our study, which indicates that whole blood concentrations do not accurately predict CSA concentrations in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with those of a previous prospective study of CsA-ME vs. tacrolimus that showed no significant difference in rejection rates between the 2 therapies in liver transplant recipients, even when CsA-ME is monitored by C 0 level. 6 Improved protection against rejection has been reported with C 2 monitoring compared to C 0 monitoring in liver transplantation, 8 and it is feasible that earlier reports of inferior graft outcome with CsA-ME may have been the result of inappropriate exposure levels. 5 However, more patients withdrew from the CsA-ME group, most frequently as a consequence of adverse events, although the number and severity of adverse events were similar in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…A number of trials have employed C 2 monitoring in solid organ transplantation [58][59][60] and demonstrated superior outcomes in terms of rejection rates and acute toxicities compared to trough-level monitoring. This has led some to conclude that C 2 monitoring is now the optimal method of monitoring oral CsA in the setting of de novo renal and hepatic transplants.…”
Section: Cyclosporin Monitoring In the Setting Of Solid Organ Transplmentioning
confidence: 99%